KEBERLANJUTAN USAHA BATIK MOTIF KHAS DESA KENONGO MELALUI TRANSAKSI MINIM KONTAK - Masruchin; Fitrinur Latifah; Muhammad Ruslianor maika Maika; Qanitah An Nabila A’yun; Cindy Cintania Amerta; Nafisah Maulidiah Chusna (LP2M Universitas Hasanuddin, 2022)
On October 2, 2009, UNESCO established a human heritage for oral and non-material culture, namely Batik, this is genuinely proud for the Indonesian people, and we are obliged to preserve it. Kenongo is a village in Sidoarjo Regency formerly; in the 1970s, it was a center for Batik craftsmen with several patented batik motifs typical of Kenongo village. Currently, there is only one batik shop still operational, namely Batik Sari Kenongo. The store is currently experiencing an extraordinary decline in turnover due to the Covid-19 pandemic so that it has laid off its employees. The results of our team's observations of their partners have not implemented online marketing so that the community service program for excellence in Islamic Banking Study Program Universitas Muhammadiyah Sidoarjo raised the title